Civic Medicine Physician, Polity, and Pen in Early Modern Europe - Mendelsohn, J. Andrew; Kinzelbach, Annemarie; Schilling, Ruth (Routledge / Asian Studies Association of Australia (ASAA) South Asian Series, 2020)
Communities great and small across Europe for eight centuries have contracted with doctors. Physicians provided citizen care, helped govern, and often led in public life. Civic Medicine stakes out this timely subject by focusing on its golden age, when cities rivaled territorial states in local and global Europe and when civic doctors were central to the rise of shared, organized written information about the human and natural world. This opens the prospect of a long history of knowledge and action shaped more by community and responsibility than market or state, exchange or power.